THE EFFECTIVENESS OF THE PROJECT-BASED LEARNING MODEL ON THE CIVIC EDUCATION LEARNING OUTCOMES OF FIFTH-GRADE STUDENTS AT SEJAHTERA ELEMENTARY SCHOOL - Dindha Aulia Rivai; Nurrohmatul Amaliyah (Jurnal Visipena, 2026)
This study aimed to measure the effectiveness of the Project-Based Learning Model in Civic Education (PKN) learning methods for fifth-grade students at SDS Sejahtera. The main objective of this research was to determine whether Project-Based Learning could improve students’ learning outcomes. The methodology used in this study was a correlational analysis with a saturated sampling approach. The instruments consisted of 30 questionnaire items related to Project-Based Learning, 20 social studies essay questions, and 10 multiple-choice questions. Instrument validity was tested using the Pearson Product Moment correlation, while reliability was measured using the Cronbach’s Alpha formula. The reliability coefficients obtained were 0.733 for the Project-Based Learning instrument and 0.674 for the social studies instrument. The results of the analysis showed an r-count value of 0.577 with a p-value of 0.000, indicating a significant correlation between Project-Based Learning and Civic Education learning methods. The t-test result showed t = 4.900 with a p-value of 0.000, meaning that H0 was rejected and Project-Based Learning was proven to be effective. Furthermore, the analysis revealed an F-count value of 24.011 and an R² value of 33.3%, indicating a significant influence between the two variables. In conclusion, this study demonstrates that Project-Based Learning is an effective method for improving the Civic Education learning outcomes of fifth-grade students at SDS Sejahtera. This learning model has the potential to be implemented more broadly in other learning contexts.